Metabolic dysfunction-associated steatotic liver disease and gastroesophageal reflux disease: a mendelian randomization study in European and East Asian populations - Su, Chen’guang; Liao, Zheng; Li, Hewen; Pei, Yinxuan; Wang, Zixiang; Li, Jian; Liu, Jinlong (Frontiers in Genetics, 2024)
BackgroundNumerous observational studies have shown a potential association between metabolic dysfunction-associated steatotic liver disease (MASLD) and gastroesophageal reflux disease (GERD). However, causality is unclear. This study utilized genome-wide association study (GWAS) genetic data to explore the causal relationship between MASLD and GERD in European and East Asian populations.MethodsThis study utilized a bidirectional, two-sample Mendelian randomization (MR) approach. All disease data were obtained from the GWAS database, and single nucleotide polymorphisms strongly associated with exposure were selected as instrumental variables. The inverse variance weighted (IVW) method is primarily utilized to evaluate the causal relationship between exposure and outcome. Finally, sensitivity analyses were performed to ensure the robustness of the results.ResultsThe IVW estimates indicated that non-alcoholic fatty liver disease (NAFLD) (odds ratio (OR) = 1.054, 95% confidence interval (CI), 0.966–1.150, p = 0.236) and percent liver fat (OR = 0.977, 95% CI, 0.937–1.018, p = 0.258) in European population were not linked to a higher risk of GERD. However, GERD in European population was associated with an increased risk of NAFLD (OR = 1.485, 95% CI, 1.274–1.729, p < 0.001) and percent liver fat (OR = 1.244, 95% CI, 1.171–1.321, p < 0.001). In addition, the IVW analysis in East Asian population showed that alanine aminotransferase (ALT) was associated with an increased risk of GERD (OR = 2.305, 95% CI, 1.241–4.281, p = 0.008), whereas aspartate aminotransferase (AST) had no causal effects on GERD risk (OR = 0.973, 95% CI, 0.541–1.749, p = 0.926). Furthermore, the associations between GERD and ALT (OR = 1.007, 95% CI, 0.998–1.015, p = 0.123) or AST (OR = 1.004, 95% CI, 0.997–1.012, p = 0.246) were not significant. After removing outliers, a significant correlation between GERD and ALT was observed (OR = 1.009, 95% CI, 1.001–1.016, p = 0.020).ConclusionThere was reverse causality between MASLD and GERD in European population, while there was bidirectional causality between a proxie for MASLD (ALT) and GERD in East Asian population. This study can provide novel insights into cross-ethnic genetic research on MASLD and GERD.